Manipulacija u političkom diskursu / Manipulation In Political Discourse: govor „Zenga“ Muammara al-Gaddafija / Muammar Al-Gaddafi's Speech Zenga (Context: Journal of Interdisciplinary Studies, 2022)
Manipulation is a kind of speech activity which has definite intentions and aims, such as gaining control and power within political discourse. This paper will shed light on the theoretical ground on which this phenomenon is based to determine how language is utilized for manipulation. The analysis aims to investigate manipulative strategies and the language devices used in generating these strategies in al-Gaddafi s speech known as Zenga. Also, it will pay more attention to strategy of polarisation, i.e. basic strategy of positive self-presentation and negative other-presentation. This paper will be limited to lexical-semantic devices (selection of negative words for them and positive words for us), certain grammatical mechanisms (passive, nominalisation) and rhetorical devices (metaphor, metonymy, hyperbole). The study shows the diversity of modes of how language of the speech is manipulated on diffe ent levels of discourse.